Site-directed spin labeling of a bacterial chemoreceptor reveals a dynamic, loosely packed transmembrane domain - Barnakov, Alexander (Cold Spring Harbor Laboratory Press, 2002)
We used site-directed spin labeling and electron paramagnetic resonance spectroscopy to investigate dynamics and helical packing in the four-helix transmembrane domain of the homodimeric bacterial chemoreceptor Trg. We focused on the first transmembrane helix, TM1, particularly on the nine-residue sequence nearest the periplasm, because patterns of disulfide formation between introduced cysteines had identified that segment as the region of closest approach among neighboring transmembrane helices. Along this sequence, mobility and accessibility of the introduced spin label were characteristic of loosely packed or solvent-exposed side chains. This was also the case for eight additional positions around the circumference and along the length of TM1. For the continuous nine-residue sequence near the periplasm, mobility and accessibility varied only modestly as a function of position. We conclude that side chains of TM1 that face the interior of the four-helix domain interact with neighboring helices but dynamic movement results in loose packing. Compared to transmembrane segments of other membrane proteins reconstituted into lipid bilayers and characterized by site-directed spin labeling, TM1 of chemoreceptor Trg is the most dynamic and loosely packed. A dynamic, loosely packed chemoreceptor domain can account for many experimental observations about the transmembrane domains of chemoreceptors.